Influence of Implant Angulation With Different Crowns on Stress Distribution - Pellizzer, Eduardo Piza [UNESP]; Falcon-Antenucci, Rosse Mary; Perri de Carvalho, Paulo Sergio [UNESP]; Inatomi Kavano Sanchez, Daniela Mayumi; Tozo Rinaldi, Gabriel Augusto; de Aguirre, Carolina Calles; Goiato, Marcelo Coelho [UNESP] (Lippincott Williams & Wilkins, 2011)
The aim of this study was to perform a photoelastic analysis of stress distribution on straight and angulated implants with different crowns (screwed and cemented). Three models were made of photoelastic resin PL-2: model 1: external hexagon implant 3.75 x 10.00 mm at 0 degrees; model 2: external hexagon implant 3.75 x 10.00 mm at 17 degrees; model 3: external hexagon implant 3.75 x 10.00 mm at 30 degrees. Axial and oblique (45 degrees) load (100 N) was applied with a universal testing machine. The photoelastic fringes on the models were recorded with a digital camera and visualized in a graphic software for qualitative analysis. The axial loading generated the same pattern of stress distribution. The highest stresses were concentrated between medium and apical thirds. The oblique loading generated a similar pattern of stress distribution in the models with similar implant angulation; the highest stress was located on the cervical region opposite to implant angulation and on the apical third. It was concluded that the higher the implant angulation, the higher the stress value, independent of crown type. The screwed prostheses exhibited the highest stress concentration. The oblique load generated higher stress value and concentration than the axial load.
Keywords: Dental implant; implant angulation; cement retention; screw retention; photoelasticity; biomechanics